Circularly Polarized Ultra-Wideband Antenna for Uni-Traveling-Carrier Photodiode Terahertz Source - Qi Li; Chuang Nie; Zihao Liu; Xin Zhou; Xiaohe Cheng; Song Liang; Yuan Yao (Sensors, 2023)
This paper proposes a circularly polarized ultra-wideband (UWB) antenna for a Uni-Traveling-Carrier Photodiode (UTC-PD) to meet the growing demand for bandwidth and polarization diversity in terahertz (THz) communication. In the design of the UTC-PD integrated antenna, the planar electrodes of the chip are directly integrated with the antenna to simplify the integration process. However, this integration introduces new problems, such as asymmetry inside the spiral antenna, which leads to a deterioration in the corresponding high-frequency performance. To address this issue, the antenna’s structure is optimized, and a lens is integrated to enhance directivity and eliminate surface waves. As a result, the proposed antenna achieves a 100–1500 GHz (175%) impedance bandwidth and a 150–720 GHz (131%) axial ratio bandwidth for the UTC-PD. The maximum gain of the antenna is 21.05 dBi at 1 THz.